2014
DOI: 10.1136/bcr-2014-205462
|View full text |Cite
|
Sign up to set email alerts
|

ACE inhibitors: upper respiratory symptoms

Abstract: Cough and angioedema are well-known adverse reactions of ACE inhibitors. However, other adverse effects of upper airways such as postnasal drainage, rhinitis and nasal blockage, are less frequently recognised. These might share the same pathophysiological mechanism: bradykinin accumulation. We present two patients with ACE inhibitor-induced upper respiratory symptoms that improved after the discontinuation of ACE-inhibitors and substitution with angiotensin II receptor blockers. The incidence of these adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…147 No mechanism has been clearly identified because there are many drugs that can produce nasal symptoms, such as calcium channel blockers, angiotensin-converting enzyme inhibitors, gabapentin, and psychotropics (eg, risperidone and chlorpromazine). 147,148 The effect of exogenous estrogens and oral contraceptives on nasal physiology is uncertain although it has been suggested that oral contraceptives may reduce allergen-provoked nasal congestion during ovulation but increase sneezing at the end of the menstrual cycle. [149][150][151] Overuse of topical decongestants can result in rhinitis medicamentosa, a form of drug-induced rhinitis, which is further discussed in the intranasal decongestants section.…”
Section: Drug-induced Rhinitismentioning
confidence: 99%
See 1 more Smart Citation
“…147 No mechanism has been clearly identified because there are many drugs that can produce nasal symptoms, such as calcium channel blockers, angiotensin-converting enzyme inhibitors, gabapentin, and psychotropics (eg, risperidone and chlorpromazine). 147,148 The effect of exogenous estrogens and oral contraceptives on nasal physiology is uncertain although it has been suggested that oral contraceptives may reduce allergen-provoked nasal congestion during ovulation but increase sneezing at the end of the menstrual cycle. [149][150][151] Overuse of topical decongestants can result in rhinitis medicamentosa, a form of drug-induced rhinitis, which is further discussed in the intranasal decongestants section.…”
Section: Drug-induced Rhinitismentioning
confidence: 99%
“…In addition to AR, because of the concomitant use of multiple medications in the elderly, drug-induced rhinitis is not infrequent. Alpha-1 adrenergic antagonists used for benign prostatic hyperplasia, 566 angiotensin-converting enzyme inhibitors, 148,[567][568][569] and possibly beta-adrenergic inhibitors 570 and phosphodiesterase inhibitors 571 can induce symptoms of rhinitis. (See earlier section on drug-induced rhinitis.…”
Section: Elderly Patients and Rhinitismentioning
confidence: 99%
“…In the present case, our patient was a chronic user of ACE inhibitors and had no comorbidity. On the other hand, patients with severe edema, particularly in the upper airway, may require either mechanical ventilation or an invasive procedure such as tracheotomy, intubation, or cricothyroidotomy [ 18 , 19 ]. However, in this patient the administration of antihistamines and corticosteroids brought about a resolution.…”
Section: Discussionmentioning
confidence: 99%
“…ad 1) Prazosin, terazosin, doxazosin, alfuzosin, ad 2) Nifedipine, lacidipine, diltiazem and 3): These medicaments were already discussed in Doty's reviews New references are …”
Section: Zinc Gluconate Copper Gluconate Magnesium Gluconatementioning
confidence: 99%